Propuesta turística para los miradores urbanos, de la ciudad de Loja - Ojeda Abrigo, María Belén (2023)
Loja is one of the oldest cities in the country and capital of the province of Loja, was founded in the valley of Cuxibamba by the Spanish captain and explorer Alonso de Mercadillo in 1548. Due to its geographical location and landscape characteristics, visitors can know the city from another perspective, that is, from the urban viewpoints that exist in the city, thanks to these you can get a real perspective of the city, you can enhance the natural, social and economic resources that make it up, also causes the enjoyment of people to observe the city from a panoramic view with a pleasant atmosphere, that is why the following general objective was raised: To establish a tourist proposal for the urban viewpoints of the city of Loja and supported with two specific objectives which were: to analyze the current situation of the urban viewpoints as tourist resources of the city of Loja and to define strategies for the improvement of the urban viewpoints. A methodology was used based on the tourist diagnosis card of the destination proposed by the MINTUR, adapting it for viewpoints, an analysis was made according to the criteria of selection, purification and screening to determine which viewpoints need improvement, surveys, interviews and to determine the strategies a PESTEL analysis, SWOT analysis and cross SWOT analysis were carried out, With these analyses it was possible to determine four strategic objectives that will allow the improvement of the viewpoints to have new experiences when visiting these places, thus concluding that, currently the urban viewpoints of the city are in a regular state since there is no maintenance by the authorities and it is necessary to increase a security system, also thanks to the location of the viewpoints it was possible to create a tourist route.